A STUDY ON THE USE OF E-RESOURCES BY UNIVERSITY STUDENTS IN SELECTED INDIAN UNIVERSITIES - Dr. Mahesh Devanandbhai Nandaniya (International Educational Journal of Science and Engineering, 2025)
The rapid advancement of information and communication technologies has significantly transformed the landscape of higher education and academic libraries. Electronic resources (e-resources) such as e-journals, e-books, online databases, digital repositories, and other web-based information platforms have become essential tools for learning, teaching, and research. University students increasingly rely on these digital resources to access scholarly information quickly and efficiently. This paper aims to examine the role and significance of e-resources in supporting the academic and research needs of university students in selected Indian universities. The study is conceptual in nature and is based on the review of existing literature, reports, and scholarly discussions related to the use of electronic resources in higher education. The paper highlights the different types of e-resources available in academic libraries, their advantages over traditional print resources, and the major digital initiatives undertaken in India to promote access to electronic information. It also discusses the common challenges faced by students, such as lack of awareness, limited digital literacy, and infrastructure constraints. The study emphasizes the crucial role of university libraries and librarians in promoting awareness, providing training, and facilitating effective utilization of e-resources to enhance academic learning and research productivity among students.